2013
DOI: 10.1007/s00784-013-1098-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CAD/CAM all-ceramic materials on cell viability, migration ability and adenylate kinase release of human gingival fibroblasts and oral keratinocytes

Abstract: CAD/CAM all-ceramic materials can influence oral cell lines responsible for soft tissue creation which may affect the esthetic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 29 publications
0
38
1
Order By: Relevance
“…Pabst et al investigated the influence of four CAD/CAM all‐ceramic (e.max CAD LT, e.max CAD HT, Empress CAD, Mark II) materials on cell viability. According to their MTT assay results for human gingival fibroblasts in all material groups, cell viability showed no significant decrease at all time periods (3, 6, 9, and 12 days) . In the results of this study, only the Empress CAD group presented a significant decrease in cell viability for the 7 th day of the test period.…”
Section: Discussioncontrasting
confidence: 71%
“…Pabst et al investigated the influence of four CAD/CAM all‐ceramic (e.max CAD LT, e.max CAD HT, Empress CAD, Mark II) materials on cell viability. According to their MTT assay results for human gingival fibroblasts in all material groups, cell viability showed no significant decrease at all time periods (3, 6, 9, and 12 days) . In the results of this study, only the Empress CAD group presented a significant decrease in cell viability for the 7 th day of the test period.…”
Section: Discussioncontrasting
confidence: 71%
“…Actually, titanium is a gold-standard material in the field of dental implant prosthodontics mainly due to its high corrosion resistance, low toxicity, very low allergenic potential and good biocompatibility properties (Jorge et al 2013). Regarding lithium disilicate glassceramic, HGF behavior on this material has been poorly studied (Brackett et al 2008;Pabst et al 2014;Tetè et al 2014). The present results showed a good cellular attachment on lithium disilicate glass-ceramic but a slower proliferation than on titanium.…”
Section: Discussionmentioning
confidence: 99%
“…To author's knowledge there is no study comparing the attachment and proliferation of HGFs on titanium and on lithium disilicate glass-ceramic. Tetè et al (2014) reported that lithium disilicate glass-ceramic shows a lower cytocompatibility than zirconia and other authors observed that this material shows cytotoxic effects (Brackett et al 2008;Pabst et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Among the dental ceramics, zirconia was introduced with the purpose of meeting the requirements of aesthetics and resistance, and its use has been widely disseminated in conjunction with computer-aided design/ computer-assisted manufacturing (CAD/CAM) systems (4). Resin-matrix ceramics or indirect composites for CAD/CAM applications can be classified according to their microstructure into dispersed fillers (zirconia-silica nanofillers and organic matrix) and polymer-infiltratedceramic-networks (PICNs), based on the infiltration of a pre-sintered glass-ceramic scaffold with a polymeric material (5).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the in vitro cellular responses to several types of dental ceramics in use have not always been favorable (11). The CAD/CAMmilled, all-ceramic materials used in implant abutments come in close contact with oral soft tissues such as the keratinized marginal gingiva, which may raise concerns about the safety and biocompatibility of these products (4). According to Tassin et al (12), significant cytotoxicity may be observed for conventional composites, while PICNs such as Vita Enamic proved to be very biocompatible during in vitro assays.…”
Section: Introductionmentioning
confidence: 99%